Integrated design optimization of spar floating wind turbines - Hegseth, John Marius; Bachynski, Erin E.; Martins, Joaquim R.R.A. (Marine structures, 2020)
A linearized aero-hydro-servo-elastic floating wind turbine model is presented and used to perform integrated design optimization of the platform, tower, mooring system, and blade-pitch controller for a 10 MW spar floating wind turbine. Optimal design solutions are found using gradient-based optimization with analytic derivatives, considering both fatigue and extreme response constraints, where the objective function is a weighted combination of system cost and power quality. Optimization results show that local minima exist both in the soft-stiff and stiff-stiff range for the first tower bending mode and that a stiff-stiff tower design is needed to reach a solution that satisfies the fatigue constraints. The optimized platform has a relatively small diameter in the wave zone to limit the wave loads on the structure and an hourglass shape far below the waterline. The shape increases the restoring moment and natural frequency in pitch, which leads to improved behaviour in the low-frequency range. The importance of integrated optimization is shown in the solutions for the tower and blade-pitch control system, which are clearly affected by the simultaneous design of the platform. State-of-the-art nonlinear time-domain analyses show that the linearized model is conservative in general, but reasonably accurate in capturing trends, suggesting that the presented methodology is suitable for preliminary integrated design calculations. •A linearized aero-hydro-servo-elastic floating wind turbine model was developed.•Integrated design was performed using gradient-based optimization.•A stiff-stiff tower design was needed to satisfy fatigue constraints.•Tower and blade-pitch controller were affected by the integrated design process.•Optimized design was verified using nonlinear time-domain simulations.